0060 Morning Locus Coeruleus Activation During the PVT Predicts Later-Day Sleepiness. (27th May 2020) - Lei, H; Quan, P; Liu, W; Zhang, X; Chai, Y; Yang, F; Dinges, D; Rao, H
Abstract: Introduction: The locus coeruleus (LC) plays a key role in the regulation of arousal and autonomic function. Homeostatic sleep pressure refers to the drive for sleep that increases as a saturating exponential when we stay awake and decreases exponentially when we sleep. The current study used arterial spin labeling (ASL) functional magnetic resonance imaging (fMRI) to investigate the relationship between homeostatic sleep pressure (sleepiness) and LC activity during the psychomotor vigilance test (PVT). Methods: We analyzed sleepiness and ASL imaging data from N=70 health adults (40 males, age range 21–50 years) who participated in a controlled in-laboratory sleep study. All participants were scanned at rest and during the PVT on the morning between 0700h-1000h after 9 hour time-in-bed (TIB) baseline sleep. LC regions-of-interest (ROI) were defined by standard templates from Keren et al. (2009). Sleepiness was assessed by the Karolinska Sleepiness Scale (KSS) every two hours from 10:30 am to 10:30 pm. Results: Sleepiness scores gradually increased over wakefulness time and reached its peak in the evening at about 10:20pm. PVT-induced CBF changes did not correlate with sleepiness scores on the morning (p > 0.05), but showed significant negative correlations with sleepiness scores on later day when sleep pressure became higher, especially during the night-time (r = -0.41, p < 0.001). Specifically, LC CBF showed significant increases during the PVT scan as compared to the resting scan (p = 0.04) in individuals with less nigh-time sleepiness (KSS < 4), but no differences (p > 0.1) in individuals with greater nigh-time sleepiness (KSS ≥ 5). After controlling for age, gender, and total sleep time, PVT-induced regional CBF difference in the LC still negatively predicted sleepiness (β = -0.325, p = 0.005). Conclusion: Our findings showed that individuals with greater LC CBF increases during the PVT were less sleepy during the night, supporting the key role of LC activity in promoting wakefulness and maintaining sleep homeostasis. PVT-induced LC activation may provide a non-invasive bio-marker of homeostatic sleep pressure in healthy adults. Support: Supported in part by NIH grants R01-HL102119, R01-MH107571, R21-AG051981. CTRC UL1RR024134, and P30-NS045839.